Características de las maloclusiones esqueléticas en pacientes diagnosticados con SAHOS durante el año 2021-I en un centro de diagnóstico en el departamento del Quindío (2022)
The main purpose of this study was able to determine the skeletal characteristics of patients with obstructive sleep apnea syndrome (OSAS) who were diagnosed during the year 2021-I in a sleep disorders diagnostic center in the Armenia, Quindío city. To develop this research, extraoral lateral skull radiographs were taken in 44 patients with a confirmed OSAS diagnosis, BMI<30 kg/m2 and not history of airway pathology. From these X-rays, a cephalometric analysis was performed including linear and angular measurements to classify patients into each type of skeletal malocclusion, to establish the size and length of the maxilla and mandible, and to confirm the upper and lower airway size. In order to determine the relationship between skeletal malocclusion and the presence of moderate to severe OSAS, statistical significance test was performed (Fisher), these showed the independence of the two variables (p=0.447). The Anova test analysis of variance was carried out to establish whether each severity SAHOS group presented completely different characteristics with respect to the other subgroups, it only showed significant differences to the SNA variable (p=0,001). Finally, it was established that 68,2% (n=30) of OSAS patients in the sample presented decreased mandibular length. While the 59,1% (n=26) showed the decreased on maxillary length. Regarding the upper airway, a decrease was found in 95.5% of the OSAS patients (n=42). No significant differences were found in the lower airway.